2015
DOI: 10.1111/cen.12694
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone secretion decreases with age in paediatric Prader‐Willi syndrome

Abstract: The utility of performing GH stimulation tests as an indication of GH status under 18 months of age in Prader-Willi syndrome is questionable. If performed, results should be carefully interpreted in the context of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…It is likely that there is a combination of subnormal GH reserve and IGF-1 generation in individuals with PWS leading to subnormal growth response. Pituitary GH reserve may progressively decline with age in PWS children and GH levels are noted to be relatively lower in obese PWS patients than those who are non-obese (7). Additionally, one study has shown genotypic differences in GH secretary responses on GH stimulation testing, with higher GH response in PWS patients with paternal deletion of 15q11-q13 than in those with maternal UPD15 (8).…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%
“…It is likely that there is a combination of subnormal GH reserve and IGF-1 generation in individuals with PWS leading to subnormal growth response. Pituitary GH reserve may progressively decline with age in PWS children and GH levels are noted to be relatively lower in obese PWS patients than those who are non-obese (7). Additionally, one study has shown genotypic differences in GH secretary responses on GH stimulation testing, with higher GH response in PWS patients with paternal deletion of 15q11-q13 than in those with maternal UPD15 (8).…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%
“…One of these studies in 27 children with PWS also performed a combined test (GHRH‐arginine or GHRH‐pyridostigmine test), which showed a much lower prevalence of GHD (15%) than the clonidine and arginine tests . As studies in adults with PWS have described a higher prevalence of GHD after combined stimulation tests, the authors of both studies suggested that GHD in PWS might be due to an evolving process, with pituitary GH reserve decreasing with age . Although we did not perform GH stimulation tests during childhood before starting GH treatment, our data show that, of the 18 children with an IGF‐I <−2 SDS at start of GH treatment, all but two patients had normal serum IGF‐I levels (>−2 SDS) after cessation of GH at adult height attainment.…”
Section: Discussionmentioning
confidence: 74%
“…Two studies in young children with PWS described a low GH peak after clonidine or arginine in 68%‐85% . One of these studies in 27 children with PWS also performed a combined test (GHRH‐arginine or GHRH‐pyridostigmine test), which showed a much lower prevalence of GHD (15%) than the clonidine and arginine tests .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 These findings seem to support the hypothesis that GH pituitary reserve, which is still preserved in young patients, gradually declines with age, suggesting that GHD in PWS may be due to an evolving process. 16 Another critical point is related to the concomitant presence of obesity, which is characterized per se by reduced GH secretion. A higher prevalence of GHD is detected in obese PWS children compared with nonobese subjects.…”
Section: Gh and Childhoodmentioning
confidence: 99%